Back and forth and forward: Metareference in recent film adaptations. (1st July 2014) - Faubert, Patrick
This article explores the phenomenon of metareference within two recent adaptations, Sherlock Holmes: A Game of Shadows (2011) and The Adventures of Tintin (2011), each of which adapts a body of work already adapted across a wide range of media. This article argues that by employing metareference, a self-reflexive strategy that seeks to engender an awareness of media properties among audiences, these films self-reflexively address cinema's potential as a medium for adaptation. However, rather than marshalling these films in an assertion of cinema's superiority, this article suggests that they explore anxieties over cinema's changing position in the media landscape, ultimately reflecting broad shifts in our perception of film adaptation.